Chlorhexidine droplet splash from a skin preparation gallipot: effect of height of pouring. (1st October 2013) - Evans, L.; Cunningham, M.; Tilakaratna, P.
Summary Chlorhexidine contamination of equipment used in central neuraxial anaesthesia has been implicated in causing adhesive arachnoiditis. We measured the extent of chlorhexidine splash during pouring into a gallipot (antiseptic skin preparation container) from heights of 5 cm, 10 cm, 15 cm and 20 cm. Twenty experiments were performed at each height. Measurements made up to a horizontal distance of 40 cm radius from the gallipot showed a median (IQR [range]) maximum spread of splash droplets ≥ 2 mm diameter of 26.2 (10.2–36.4 [0–40]) cm. The 40‐cm radius measurement area was divided into 5‐cm‐wide zones to assess spread. At pouring heights of 15 cm and 20 cm, all zones were contaminated. These results demonstrate that pouring chlorhexidine into a gallipot generates significant splash, and we recommend that this should be avoided near equipment used for neuraxial anaesthesia.